Project #sextoupedagógico for teachers in the municipal school system of Benevides, Pará, Brazil - Calderaro, Kelly Lene Lopes; Silva, Francilene Sodré da; Sampaio, Antonia Roberta Mitre; Pompeu, Josué Lacerda (Seven Editora, 2024)
Education is related to activities that provide the student’s learning as a way of fully constructing the subject. In this context, the Pedagogy of Projects emerges, a systematic teaching and learning system that is characterized by the systematized conduction of techniques and activities that promote the construction of knowledge. Thus, the present study aimed to analyze the importance of projects in education, emphasizing the role of school management in conducting this methodology. To conduct this work, a bibliographic research was carried out, from which it can be pointed to the fact that Project Pedagogy, despite being a methodology that has been used and disseminated in the educational environment for a long time, still encounters resistance in many school institutions. This fact indicates the need for school management to assume its role in the pedagogical qualification of schools and to equip its teachers to work with projects. This can happen through the organization of times and spaces, the awareness of the school community and the in-service training of teachers, in order to achieve a culture of projects in the school environment. DOI:https://doi.org/10.56238/sevened2023.006-128